High Performance Self-Consolidating Cementitious Composites - Kodeboyina, Ganesh Babu; Taylor and Francis (Boca Raton, FL : CRC Press, 2018)
This book attempts to bring together some of the basic intricacies in the production of the complete range of self-consolidating cementitious composites, with a proper understanding of the contributions of different materials and their combinations, including performance and limitations. Presents a comprehensive perspective of the state of the art in self-compacting concretes while explaining the basic background and principles, includes possible alternatives of making SCC with different powder extenders and pozzolanic materials. Explores concepts through theoretical and graphical representations
1. INTRODUCTION -- 1.1. The concept -- 1.2. Historical development -- 1.3. The definitions -- 1.4. Formulations and classification of SCCs -- 1.5. Potential and limitations -- 1.6. Future prospects -- References -- 2. CONSTITUENT MATERIALS -- 2.1. Constituent materials and availability -- 2.2. Cements and characteristics -- 2.3. Simple powder extenders -- 2.4. Supplementary cementitious materials -- 2.5. Superplasticizers and other chemical admixtures -- 2.6. Aggregate characteristics -- 2.7. Interactions and compatibility -- References -- 3. INSIGHTS INTO STANDARDS AND SPECIFICATIONS -- 3.1. Standardization principles -- 3.2. Fundamental characterization and classification -- 3.3. Methods of consistency measurement -- 3.4. Japanese recommendations -- 3.5. Euro-EFNARC guidelines -- 3.6. ACI recommendations -- 3.7. Other perceptions -- 3.8. Summary and suggestions -- References -- 4. METHODOLOGIES FOR THE PROPORTIONING OF SCC MIXTURES -- 4.1. Introduction -- 4.2. Design viewpoints -- 4.3. Semi-empirical methods -- 4.4. Compositions based on wetting water requirements of the constituents -- 4.5. Methods based on aggregate distribution and packing factors -- 4.6. Methods of limiting the cementitious materials through water content -- 4.7. Methods of incorporating the cementitious efficiency of pozzolans -- 4.8. Procedures for incorporating different pozzolans -- 4.9. Approaches for a specified compressive strength. -- 4.10. Methods based on rheometer tests -- 4.11. Methods based on the rheological paste model -- 4.12. Methods based on the rheological paste model incorporating fibrous materials -- 4.13. Guidelines based on statistical evaluations -- 4.14. Need for a relook and proposed methodology -- References -- 5. CONCEPTS AND CRITERIA FOR HIGH PERFORMANCE -- 5.1. Introduction -- 5.2. Fundamentals concepts of performance -- 5.3. Environmental parameters -- 5.4. Practical approach for high-performance design -- 5.5. Performance evaluation methodologies -- 5.6. Concept of pozzolanic efficiency and strength relations -- 5.7. Effects of pozzolanic addition on consistency and compaction -- 5.8. Packing and optimal granular skeleton -- 5.9. Proposed methodology and its effectiveness -- 5.10. Efficacy of the proposed methodology -- References -- 6. SCCs BASED ON POWDER EXTENDERS AND LOW-END POZZOLANS -- 6.1. Introduction -- 6.2. Concept of powder extenders -- 6.3. SCCs incorporating fly ash -- 6.4. SCCs incorporating Limestone powder -- 6.5. SCCs incorporating GGBS -- 6.6. SCCs through other inert powder extenders -- 6.7. Practical limitations on powder fillers -- References -- 7. SCCs BASED ON HIGH EFFICIENCY AND NANO POZZOLANS -- 7.1. Introduction -- 7.2. High strength and high performance concepts -- 7.3. SCCs incorporating silica fume and Nano silica -- 7.4. SCCs incorporating metakaolin -- 7.5. SCCs incorporating rice husk ash -- 7.6. Saturation concepts and effects -- 7.7. SCCs incorporating fibrous constituents -- References -- 8. FRESH CONCRETE CHARACTERISTICS OF SCC -- 8.1. Introduction -- 8.2. Fundamentals of consistency and compaction -- 8.3. Rheology and thixotropy of SCCs -- 8.4. Critical evaluation and comparison of the test methods -- 8.5. Effects of quality and quantity of cementitious materials -- 8.6. Wetting water requirements of powder materials -- 8.7. Effects of granular skeleton characteristics and fibrous materials -- 8.8. Segregation and bleeding -- 8.9. Shrinkage and heat of hydration -- 8.10. Transport, placement and finishing -- 8.11. Formwork and pressure on formwork -- 8.12. Setting times and removal of forms -- 8.13. Curing needs, precautions and best practices -- 8.14. Effect of accelerated curing, maturity concepts -- 8.15. Quality assurance and control -- References -- 9. MECHANICAL CHARACTERISTICS OF SCC -- 9.1. Introduction -- 9.2. Physical properties and microstructural effects -- 9.3. Compressive strength and strength gain rate -- 9.4. Near-surface characteristics -- 9.5. Tensile and shear strengths -- 9.6. Applicability of conventional concrete relations to SCC -- 9.7. Modulus of elasticity -- 9.8. Bond with reinforcement -- 9.9. Creep and relaxation -- 9.10. Prestressing and anchorages -- 9.11. Applicability of NDT -- References -- 10. PERFORMANCE AND SERVICE-LIFE OF SCC -- 10.1. Introduction -- 10.2. Durability of concrete -- 10.3. Strength and porosity -- 10.4. Transport characteristics -- 10.5. Environmental degradation -- 10.6. Chemical degradation -- 10.7. Alkali-aggregate reactivity -- 10.8. Thermal degradation -- 10.9. Corrosion characteristics -- 10.10. Service-life prediction or Residual life evaluation methods -- References -- 11. FRONTIERS AND RESEARCH NEEDS -- 11.1. Introduction -- 11.2. Applications and prospects -- 11.3. SCCs in repair and rehabilitation practice -- 11.4. Re-alkalization of concrete -- 11.5. Chloride binding and extraction -- 11.6. Tunnel lining and grouting applications -- 11.7. Underwater concrete applications and repair -- 11.8. Applications in marine environment -- 11.9. Ultrahigh strength grouts and composites -- 11.10. Reinforced fibrous composites -- 11.11. Research and developmental requirements -- 11.12. Concluding remarks -- References.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Construction / General; TECHNOLOGY & ENGINEERING / Material Science; Cement composites; Electronic books